2017
DOI: 10.1016/j.jclepro.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

‘Nudging’ as an architect of more responsible consumer choice in food service provision: The role of restaurant menu design

Abstract: The sector of food service provision generates substantial environmental and societal impacts. Environmental impacts are particularly pronounced in terms of carbon footprint build-up while societal impacts are reflected in often unhealthy food choice. These impacts should be minimised to facilitate progress of the sector towards sustainability. A significant share of the negative impacts from food service provision is attributed to irresponsible consumer choice which needs to be architected and made more socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 86 publications
6
49
0
Order By: Relevance
“…Therefore, providing information about menu items has the potential to educate consumers (Roberto, Larsen, Agnew, Baik, & Brownell, 2010), and increase sales of desirable items. Restaurant menus can display environmental labels to inform consumers to choose more environmentally friendly food (Filimonau et al, 2017), yet it is not common practice for restaurants to display such labels. Only one restaurant actually displays carbon labels by default: the fast-food restaurant Max-Burgers (G€ ossling & Buckley, 2016).…”
Section: Carbon Labels In Tourism and Hospitalitymentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, providing information about menu items has the potential to educate consumers (Roberto, Larsen, Agnew, Baik, & Brownell, 2010), and increase sales of desirable items. Restaurant menus can display environmental labels to inform consumers to choose more environmentally friendly food (Filimonau et al, 2017), yet it is not common practice for restaurants to display such labels. Only one restaurant actually displays carbon labels by default: the fast-food restaurant Max-Burgers (G€ ossling & Buckley, 2016).…”
Section: Carbon Labels In Tourism and Hospitalitymentioning
confidence: 99%
“…Consumers are interested in the menu item with carbon emissions labels (Lassen et al, 2016;Pulkkinen, Roininen, Katajajuuri, & J€ arvinen, 2016), but self-reported use of carbon labels is higher than actual purchase behaviour (Spaargaren et al, 2013). Diners appreciate the novelty of carbon labelling, but they remain undecided on whether or not carbon labelling drives their future decision making (Filimonau et al, 2017). The future value of carbon labelling on restaurant menus requires more research on the effects of the feasibility of carbon labels on food ordering behaviour (Filimonau et al, 2017).…”
Section: How Carbon Labels Affect Behaviourmentioning
confidence: 99%
See 3 more Smart Citations